Nazhir's Professionalism in the Management of Cash Waqf and Community Economic Empowerment - Effendi, M Rachmat; Rohmah Maulida, Ira Siti (LAA MAISYIR : Jurnal Ekonomi Islam, 2021)
This research examines Nadzir's professionalism in managing cash waqf, to map the quality of waqf institutions in the management of cash waqf in transparency and accountability in accountability to stakeholders and Allah SWT. This research uses qualitative methods through observation, interviews, and document review. The results obtained show that several Nadzir waqf, such as the Pesantren Islam Al-Azhar Foundation, the Dompet Dhafa Foundation, the Daaruttauhid Foundation, and the Semai Sinergi Ummat Foundation (Waqf Pro99), have demonstrated the management of cash waqf in a professional, transparent and accountable manner. The financial management system uses the zakat accounting standard PSAK 109. The results of an independent public accountant audit show an unqualified opinion (SWO). On average, 90% of the business results are used by social activities and community empowerment through the Wakaf Integrated Farming (WIF) program, which is focused on the field of sheep farming using the mudhorobah system. Theoretically, this research contributes to the scientific development of Islamic Institutional Management at the Faculty of Da'wah, and can be used as a reference for Nadzir waqf in managing cash waqf and waqf assets in general.